PENERAPAN METODE MARKER-BASED DAN MARKERLESS AUGMENTED REALITY PADA APLIKASI PENGENALAN ALAT KIMIA DASAR LABORATORIUM KELAS X SMKN REMBANG - Nur Moh Sholeh; Muhammad Faishol Amrulloh (SPIRIT, 2021)
Abstract:Understanding of chemical tools is very important for laboratory workers to achieve experimental goals and maintain work safety. The form of application of the method of introducing basic chemical tools at SMKN REMBANG is that students draw chemical tools in books. This method is considered less effective because it makes students feel bored and have difficulty in drawing chemical tools. Therefore, it is necessary to innovate learning methods by making applications for introducing basic laboratory chemistry tools designed using Unity3D and Vuforia with Augmented Reality technology and based-marker, markerless and mpdel waterfall methods as software development. The result of this research is to build an application for the introduction of basic chemical tools packaged in APK form. Based on the results of the pre-test, the average score was 55.7 and there was a very good improvement after the post-test with an average score of 67.7. This study obtained the value of respondents reached 87.3%..  Keywords : Augmented Reality, Laboratory Chemical, Markerless, Based Marker